Laser speckle flowgraphy can also be used to show dynamic changes in the blood flow of the skin of the foot after surgical revascularization. (June 2019) - Kikuchi, Shinsuke; Miyake, Keisuke; Tada, Yuki; Uchida, Daiki; Koya, Atsuhiro; Saito, Yukihiro; Ohura, Takehiko; Azuma, Nobuyoshi
Objectives: Laser speckle flowgraphy is a new method that enables the rapid evaluation of foot blood flow without contact with the skin. We used laser speckle flowgraphy to evaluate foot blood flow in peripheral arterial disease patients before and after surgical revascularization. Materials and methods: A prospective single-center study. Thirty-one patients with 33 limbs that underwent surgical revascularization for peripheral arterial disease were included. Pre- and postoperative foot blood flows were measured on the plantar surface via laser speckle flowgraphy and skin perfusion pressure. The laser speckle flowgraphy device was used to visualize the blood flow distribution of the target skin and processed the pulse wave velocity of synchronized heart beats. The mean blood flow, which was expressed as the area of the pulse wave as the beat strength of skin perfusion on laser speckle flowgraphy converted into a numerical value, was assessed as dynamic changes following surgery. Beat strength of skin perfusion was also investigated in non-peripheral arterial disease controls (23 patients/46 limbs). Results: The suitability of beat strength of skin perfusion in non-peripheral arterial disease controls was achieved; the beat strength of skin perfusion value was significantly higher in every area of interest in non-peripheral arterial disease controls compared to that in peripheral arterial disease limbs at the preoperative stage (105.8 ± 8.2 vs. 26.3 ± 8.2; P  < 0.01). Although the pulse wave before surgery was visually flat in peripheral arterial disease patients, the pulse wave was remarkably and immediately improved through surgical revascularization. Beat strength of skin perfusion showed a dynamic change in foot blood flow (26.3 ± 8.2 at preoperation, 98.5 ± 6.7 immediately after surgery, 107.6 ± 5.7 at seven days after surgery, P  < 0.01 for each compared to preoperation) that correlated with an improvement in skin perfusion pressure. Conclusions: Laser speckle flowgraphy is a noninvasive, contact-free modality that is easy to implement, and beat strength of skin perfusion is a useful indicator of foot circulation during the perioperative period. Further analysis with a larger number of cases is necessary to establish appropriate clinical use.